Dry eye in Parkinson's disease: a narrative review - Ungureanu, Larisa; Chaudhuri, K. Ray; Diaconu, Stefania; Falup-Pecurariu, Cristian (Frontiers in Neurology, 2023)
In Parkinson's disease (PD) patients, a wide range of ocular and visual disorders are present. Tear film instability, inflammation and dysfunction of the ocular surface, and the presence of symptoms of visual disturbance characterize dry eye, a multifactorial disease of the ocular surface. Based on a literature search, we discuss the frequency, pathogenesis, and influence on the quality of life of patients with dry eye in Parkinson's disease. Furthermore, we review the available means of diagnosis and management of dry eye. An improvement in awareness and recognition of dry eye is needed to provide suitable, personalized therapeutic options for PD patients, aiming to improve their quality of life, independence, and safety.